Innovative Leadership of The Principal in Digital Transformation and School Branding at SMAU CT Arsa Foundation Sukoharjo - Padarinda Agisma Aktifani; Istanto Istanto (FKIP - Universitas Riau, 2026)
Digital transformation and increasing competition in institutional image require school principals to demonstrate innovative leadership capable of integrating technology, school culture, and public trust. This study aims to describe the innovative leadership practices of principals in implementing digital transformation and school branding at SMAU CT ARSA Foundation Sukoharjo, a nonprofit boarding school serving students from underprivileged families. This research employed a qualitative approach, with data collected through in-depth interviews, observations, and document analysis. The findings indicate that innovative leadership is institutionalized through three main systems: (1) leadership grounded in discipline, role modeling, and school culture; (2) sustainable digital transformation oriented toward digital equity, pedagogical risk management, and digital regulation integrated with boarding school discipline; and (3) performance based school branding as an implication of successful institution building. These findings confirm that the influence of innovative leadership on school quality and reputation operates indirectly through the strengthening of organizational culture and systems. This study contributes to the field of educational leadership by demonstrating that the integration of innovative leadership, equitable digital transformation, and performance based branding constitutes an effective strategy for the sustainability of nonprofit boarding schools.